AVALIAÇÃO DA DOENÇA ARTERIAL CORONARIANA E FATORES DE RISCO CARDIOVASCULAR EM MULHERES NA PRÉ E PÓS-MENOPAUSA. - BARBOSA, Márcio Mesquita (2012)
Cardiovascular diseases are the leading cause of death in women in developed countries, with rates increasing after menopause, however, this relationship is still uncertain. The objective of this study was to investigate the difference in the prevalence of coronary heart disease among women in pre and postmenopausal women undergoing coronary angiography at the University Hospital Presidente Dutra of Federal University of Maranhão, as well as evaluating the presence of cardiovascular risk factors: diabetes, hypertension, smoking, obesity and dyslipidemia in these two groups. We developed an analytical cross-sectional study, which initially evaluated 643 women who underwent coronary angiography between May 2010 and April 2011. Data were analyzed with descriptive statistics and then compared with the chi-square test. Risk factors were assessed by Poisson regression model. Among the 460 women studied, 101 (21.97%) were premenopausal and 359 (78.1%) postmenopausal, with a mean age of the first group was 47.6 ± 6.9 years, while the second group was 64.9 ± 10.4 years. Diabetes and hypertension were more prevalent in postmenopausal women, whereas smoking was more prevalent in premenopausal women. CAD prevalence was higher in postmenopausal patients, the disease in this group was more extensive and have a most degree of obstruction. Multivariate analysis showed that older age was associated in a statistically significant increased risk of coronary artery disease and not the menopause itself. In this sample, age was the only independent factor for the increased risk of coronary artery disease.